Direct-location vs. verbal report methods for measuring auditory distance perception in the far field - Etchemendy, Pablo Esteban (2017)
In this study we evaluated whether a method of direct location is an appropriate response method for measuring auditory distance perception of far-field sound sources. We designed an experimental set-up that allows participants to indicate the distance at which they perceive the sound source by moving a visual marker. We termed this method Cross-Modal Direct Location (CMDL) since the response procedure involves the visual modality while the stimulus is presented through the auditory modality. Three experiments were conducted with sound sources located from 1 to 6 m. The first one compared the perceived distances obtained using either the CMDL device or verbal report (VR), which is the response method more frequently used for reporting auditory distance in the far field, and found differences on response compression and bias. In Experiment 2, participants reported visual distance estimates to the visual marker that were found highly accurate. Then, we asked the same group of participants to report VR estimates of auditory distance and found that the spatial visual information, obtained from the previous task, did not influence their reports. Finally, Experiment 3 compared the same responses that Experiment 1 but interleaving the methods, showing a weak, but complex, mutual influence. However, the estimates obtained with each method remained statistically different. Our results show that the auditory distance psychophysical functions obtained with the CMDL method are less susceptible to previously reported underestimation for distances over 2 m.